2011
DOI: 10.1093/pubmed/fdr088
|View full text |Cite
|
Sign up to set email alerts
|

Perceived usefulness of syndromic surveillance in Ontario during the H1N1 pandemic

Abstract: End user perceptions are valuable for identifying opportunities for improvement and guiding further investments in public health surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…From this perspective, we were unable to show that any one syndromic surveillance system was consistently more timely in detecting the outbreak than laboratory surveillance. These findings support perceptions from our survey and interviews 8,9 that information from syndromic surveillance was less timely and accurate compared to laboratory surveillance during A(H1N1)pdm09. However, we note variability in the results.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…From this perspective, we were unable to show that any one syndromic surveillance system was consistently more timely in detecting the outbreak than laboratory surveillance. These findings support perceptions from our survey and interviews 8,9 that information from syndromic surveillance was less timely and accurate compared to laboratory surveillance during A(H1N1)pdm09. However, we note variability in the results.…”
Section: Discussionsupporting
confidence: 79%
“…8 Thus, we requested aggregated data from the 18 PHUs that reported using these syndromic surveillance systems for the period April 1, 2009 to January 31, 2010, of which 13 (72%) provided data (11 provided ED visit and 8 provided school absenteeism data Telehealth about his/her 6-year-old child, the call would be recorded as age 6 and thus classified as "0-9". † 99.6% of the prescription drugs were oseltamivir, 0.4% were zanamivir.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, health departments sought to verify fewer than 15% of alerts generated from the syndromic surveillance system because the alert was obviously a false positive or resource constraints limited the ability for follow-up [14]. Lastly, a web-survey of Ontario’s 36 local public health departments, the provincial ministry of health and federal public health agency found that syndromic data were considered less useful for informing public health decisions than laboratory testing data during the 2009 influenza pandemic (A(H1N1)pdm09) [15]. Nonetheless, 70% of organizations with access to emergency department (ED) screening data felt that these data were essential for informing public health decisions on how to respond locally to A(H1N1)pdm09.…”
Section: Introductionmentioning
confidence: 99%